The Role Of Information Technology In Improving The Efficiency Of Public Services (A Case Study At The Licensing And Investment Office Of Investment Of Lahat District) - Padela, Manisa Bunga; Putri, Aulia Utami (Journal of Social Science and Humanities, 2024)
The implementation of information technology (IT) at the Investment and Licensing Office of Lahat Regency is a strategic step to enhance public service efficiency. This study aims to analyze the role of IT in accelerating administrative processes, identify the challenges faced, and seek solutions to address these issues. The method used is descriptive qualitative with data collection through in-depth interviews, observations, and documentation. The informants involved include the Head of the Office, Head of Division, and relevant staff. The results show that the implementation of IT has successfully reduced the time for licensing processes and improved service accessibility for the community. However, challenges such as limited human resources (HR) and inadequate infrastructure remain obstacles. Therefore, it is recommended that the Investment and Licensing Office conduct regular training for staff and improve IT infrastructure to maximize the benefits of technology in public services.